EFEKTIVITAS BIMBINGAN KELOMPOK SYMBOLIC MODELING FILM FRIEREN TERHADAP SOCIAL INTELLIGENCE PESERTA DIDIK - Teddy Christianto; Zakki Nurul Amin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Social intelligence is an essential ability that supports students’ success in building relationships and adapting to their social environment. However, low levels of social intelligence are still found among students, leading to difficulties in establishing social relationships and potentially hindering their developmental tasks. Although the symbolic modeling technique has been widely applied in guidance and counseling services, the use of anime as a symbolic modeling medium, particularly Frieren: Beyond Journey’s End, remains relatively underexplored. Given this gap, the present study aimed to examine the effectiveness of group guidance using the symbolic modeling technique through the film Frieren: Beyond Journey’s End in improving the social intelligence of students with low levels of social intelligence. This study employed a quasi-experimental approach with a control group time series design. The participants consisted of 14 students selected through purposive sampling and assigned to experimental and control groups. Data were collected through pretest, midtest, and posttest measurements and analyzed using Mixed Design ANOVA to examine changes in social intelligence scores across measurement periods and between groups. The results showed that group guidance using the symbolic modeling technique through the film Frieren: Beyond Journey’s End was effective in improving students’ social intelligence. Students who received the intervention demonstrated greater improvements in social intelligence than those in the control group. These findings suggest that anime films can serve as an engaging and relevant medium for group guidance interventions aimed at fostering students’ social intelligence in school settings. However, this study was limited by the relatively small sample size and the specific characteristics of the participants. ABSTRAK Social Intelligence merupakan kemampuan penting yang mendukung keberhasilan peserta didik dalam menjalin hubungan dan beradaptasi pada lingkungan sosialnya. Namun, rendahnya social intelligence masih ditemukan di kalangan peserta didik sehingga kesulitan membangun hubungan dan berpotensi mengganggu tugas perkembangannya. Meskipun teknik symbolic modeling telah digunakan dalam layanan bimbingan dan konseling, pemanfaatan media anime Frieren: Beyond Journey’s End masih relatif jarang diteliti. Oleh karena itu, penelitian ini penting dilakukan untuk mengembangkan alternatif media symbolic modeling yang lebih menarik dan relevan bagi peserta didik. Penelitian ini bertujuan untuk menguji efektivitas Bimbingan Kelompok Symbolic Modeling melalui media film Frieren: Beyond Journey’s End dalam meningkatkan social intelligence pada peserta didik yang menunjukkan tingkat social intelligence rendah. Penelitian menggunakan pendekatan kuasi eksperimen dengan desain control group time series design. Subjek penelitian berjumlah 14 peserta didik yang dipilih melalui purposive sampling dan dibagi ke dalam kelompok eksperimen dan kelompok kontrol. Pengumpulan data dalam penelitian dilaksanakan melalui pretest, midtest, dan posttest. Data penelitian dianalisis menggunakan Mixed Design ANOVA untuk mengetahui perubahan skor social intelligence berdasarkan waktu pengukuran dan perbedaan kelompok. HTemuan ini memberikan implikasi bahwa pemanfaatan film anime dalam layanan bimbingan kelompok dapat menjadi alternatif intervensi yang relevan dengan minat peserta didik untuk mengembangkan social intelligence di lingkungan sekolah. Namun, penelitian ini masih terbatas pada jumlah subjek yang relatif kecil dan karakteristik peserta didik tertentu.